2023
DOI: 10.3390/universe9070324
|View full text |Cite
|
Sign up to set email alerts
|

Vector Quarkonia at the LHC with Jethad: A High-Energy Viewpoint

Abstract: In this review, we discuss and extend the study of the inclusive production of vector quarkonia, J/ψ and Υ, emitted with large transverse momenta and rapidities at the LHC. We adopt the novel ZCW19+ determination of fragmentation functions to depict the quarkonium production mechanism at the next-to-leading level of perturbative QCD. This approach is based on the nonrelativistic QCD formalism well adapted to describe the formation of a quarkonium state from the collinear fragmentation of a gluon or a constitue… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 648 publications
0
4
0
Order By: Relevance
“…These findings mark a significant advancement in our understanding of high-energy QCD processes and offer promising prospects for future precision studies in this area. Subsequent analyses on vector quarkonia [253,254,334,335], B c mesons [314,317], and X Qq Q q tetraquarks [318], confirmed that this remarkable feature, known as natural stability of the BFKL resummation [312], comes out as basic property connected to the inclusive emission of any given heavy-flavored particle.…”
Section: Introductionmentioning
confidence: 95%
See 3 more Smart Citations
“…These findings mark a significant advancement in our understanding of high-energy QCD processes and offer promising prospects for future precision studies in this area. Subsequent analyses on vector quarkonia [253,254,334,335], B c mesons [314,317], and X Qq Q q tetraquarks [318], confirmed that this remarkable feature, known as natural stability of the BFKL resummation [312], comes out as basic property connected to the inclusive emission of any given heavy-flavored particle.…”
Section: Introductionmentioning
confidence: 95%
“…All predictions presented in this review were generated using JETHAD, a hybrid code that consistently integrates both PYTHON-and FORTRAN-based modules. JETHAD is specifically designed for computing, managing, and processing physical distributions defined within various formalisms [249,252,254,319]. Numeric calculations of differential distributions were primarily performed using FORTRAN 2008 modular routines within JETHAD, while the built-in PYTHON 3.0 analyzer was utilized for final data analysis and interpretation.…”
Section: Heavy Hadrons With Jethadmentioning
confidence: 99%
See 2 more Smart Citations